“GROWTH TRAJECTORY OF HOUSING FINANCE COMPANIES - A STUDY” (International Journal of Food and Nutritional Sciences, 2022)
Almost 50 years since the inception of HUDCO in 1970 the Housing FinanceCompanies have been playing the key role in providing financial assistance to home buyers,real estate developers for fulfilling their housing needs. For the past 6 years housing financeinstitutions are facing lot of distress due to fundamental and economic issues pertaining to theHousing sector which has led to a rising mismatch between the supply and the demand inhousing segment. Supply push factors are not lowering housing prices thus making homeownership remain elusive for the masses which has become an impediment in achievinghousing for all.Indian Economy which is relying under major stress due to various structural andcyclical issues since 2014 due to implementation of Insolvency and Bankruptcy Code,Implementation of Goods and Service Tax, Real Estate Regulation Act, Demonetisation anddue to issues such as Twin Balance Sheet Problems, Rising NPA and macro-economic issuessuch as Geo-political tensions, US-China Trade tensions which has led to the fall in Foreigndirect Investment, Real and Nominal Gross Domestic Product, Gross fixed capital Formation,Gross Private domestic investment, Rising Inflation etc., with some issues having directimpact on the Housing Finance sector, while some indirectly led to the slowdown in thesector which in turn had led to fall in the Growth of Construction industry, Cement Industry,Steel and Aluminium Industry which resulted in increased unemployment. The stress in thehousing finance institution escalated after the IL & FS crises which led banks becomereluctant in lending to the NBFC sector which led further malaise on HFIs which recently ledthe HFI [Dewan Housing Finance Institution] being moved to IBC and more importantly theimpact of Covid-19 pandemic, unprecedented lockdowns to contain the impact of Covid 19,transfer of regulation of HFCs from NHB to RBI and supply chain disruptions.In this Backdrop, at the time when people perception towards housing is changing;from no longer being possessive about the concept of home ownership with sizes of homesdecreasing drastically and micro homes. In order to overcome these challenges radicalinnovation in housing is required thus in the backdrop of gloomy economic scenario whereall the important levers of growth namely private investments, private consumptions andexports were spluttering and GDP of the country falling to a new low due to variousstructural and cyclical issue facing the economy, the authors have tried to understand thegrowth trajectory of housing finance companies between F.Y. 2011-12 to F.Y. 2020-21 andto forecast the growth trends for the year F.Y. 2029-2030, using compound annual growthrate and trend analysis as a preliminary step to the policy decisions